2008
DOI: 10.1308/003588408x321710
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Operating Time on Surgeons' Muscular Fatigue

Abstract: Surgeons should be aware that their muscular fatigue levels will increase as an operation progresses; therefore, if possible, more complex parts of the operation should be performed as early as possible, or, in the case of a very long operation, a change in surgeon may be necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 17 publications
1
44
0
Order By: Relevance
“…2 In other fields, electromyography studies in ear, nose and throat surgeons demonstrated a decrease in the mean frequency of surgeon muscle contractions in the brachioradialis and mid deltoid muscles as surgery progresses, which correlated with an increase in the muscular fatigue level. 3 In addition to physical exhaustion, mental fatigue also occurs during an operation. In other occupations in which operators must maintain a high degree of vigilance for a sustained period, such as air traffic controllers, breaks are mandated to decrease work load related stress and errors.…”
mentioning
confidence: 99%
“…2 In other fields, electromyography studies in ear, nose and throat surgeons demonstrated a decrease in the mean frequency of surgeon muscle contractions in the brachioradialis and mid deltoid muscles as surgery progresses, which correlated with an increase in the muscular fatigue level. 3 In addition to physical exhaustion, mental fatigue also occurs during an operation. In other occupations in which operators must maintain a high degree of vigilance for a sustained period, such as air traffic controllers, breaks are mandated to decrease work load related stress and errors.…”
mentioning
confidence: 99%
“…showed that operating led to an increase in fatigue in all subjects when compared to controls performing desk work. 5 In conclusion, the authors stated that muscular fatigue levels increased as an operation progressed and recommended that more complex parts of surgery be performed as early as possible or that a change in surgeon may be necessary. 5 In a study by Uhrich et al, 6 the authors looked at muscle fatigue in laparoscopic surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…5 In conclusion, the authors stated that muscular fatigue levels increased as an operation progressed and recommended that more complex parts of surgery be performed as early as possible or that a change in surgeon may be necessary. 5 In a study by Uhrich et al, 6 the authors looked at muscle fatigue in laparoscopic surgeons. The study found that atypical positions assumed by laparoscopic surgeons produced EMG amplitudes that exceeded threshold limits of acceptable muscular load, putting the surgeons at risk for fatigue and injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regards to surgical performance, fatigue can be difficult to quantify, especially in a live theatre setting. It is believed that muscular and mental fatigue can develop during prolonged operating leading to a reduction in a surgeon's fine motor control and reduced precision of instrument movement [2].…”
Section: Introductionmentioning
confidence: 99%